Research on the Impact of ESG Performance on Stock Price Volatility of Enterprises: Empirical Evidence from A-share Listed Companies - Yelaman, Mulatihan· (Transactions on Economics, Business and Management Research, 2024)
As socially responsible investment and sustainable development gain traction, the ESG performance of companies is increasingly attracting investor and public attention. ESG ratings help identify responsible firms, enabling assessment of their contributions to sustainable growth.This article examines Shanghai and Shenzhen A-share data, focusing on the impact of ESG performance on stock price volatility. Key findings include:A significant negative correlation exists between stock price volatility and ESG performance; higher ESG ratings correspond to lower volatility;he nature of property rights affects this relationship, with non-state-owned enterprises benefiting more from ESG performance in reducing volatility than state-owned enterprises;Policy uncertainty in a company’s location significantly moderates the relationship, with greater uncertainty intensifying the negative impact of ESG performance on stock price volatility.This research enhances understanding of the economic consequences of ESG performance and helps investors recognize its value, improving capital allocation efficiency.